Integrity of Election Organizers at the Crossroads: An Indonesian Case (2017–2022) - Muh Afit Khomsani (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. Professional election organizers play an essential role in realizing elections with integrity. It refers to capable, insightful, fair, transparent, accountable, and independent election bodies. However, the organizers in Indonesia are entangled with classic problems, ranging from ethical and administrative to criminal violations. Such complications lie in the biased selection process, political interventions, inter-agency relations, and other personal characteristics. This qualitative research analyzes the verdicts of the Election Organizer Ethics Council (DKPP) to examine the dynamics of election organizers and elections in Indonesia. Primary data in this study are verdicts by DKPP for 2017-2022, and the secondary ones are journal articles, scientific research, reports, and mass media publications. Data are collected and analyzed based on actor relations, regions, violation cases, and final decisions. Research findings reveal that dominant factors affect the emergence of ethical abuses by election organizers. Moreover, the research conclusion suggests enforcing moral codes for election organizers and gaps to study this topic further. Keywords: Ethics, Integrity, Election Organizers, Indonesia. Abstrak. Penyelenggara pemilihan umum (pemilu) yang berkompeten dan profesional memainkan peran penting dalam mewujudkan pemilu yang berintegritas. Hal tersebut merujuk pada penyelenggara pemilu yang cakap, berwawasan, jujur, transparan, akuntabel, mandiri, dan independen. Tetapi, dalam faktanya penyelenggara pemilu di Indonesia masih dihadapkan pada beberapa permasalahan klasik, mulai dari pelanggaran etik, administrasi, sampai dengan pidana. Permasalahan ini dipengaruhi oleh beberapa faktor, seperti permasalahan pada proses seleksi, intervensi politik, hubungan antarlembaga, dan faktor privat lainnya. Penelitian ini merupakan penelitian kualitatif dengan menganalisis putusan Dewan Kehormatan Penyelenggara Pemilu (DKPP) untuk melihat dinamika penyelenggara pemilu dan kaitannya dengan integritas pemilu di Indonesia. Data primer dalam penelitian ini adalah putusan DKPP tahun 2017-2022, sedangkan data sekunder adalah artikel, riset ilmiah, laporan penelitian, dan pemberitaan media massa. Data dikumpulkan kemudian dianalisis berdasarkan variasi aktor, pokok aduan pelanggaran, dan putusan akhir. Temuan penelitian ini menunjukkan bahwa terdapat faktor-faktor dominan yang mengakibatkan pelanggaran etik oleh penyelenggara pemilu. Kesimpulan dalam riset ini memberikan rekomendasi untuk penegakan kode etik penyelenggara Pemilu, dan celah untuk kajian selanjutnya tentang kode etik penyelenggara Pemilu. Kata Kunci: Etika, Integritas, Indonesia, Penyelenggara Pemilu.